Quantifying hepatitis C transmission risk using a new weighted scoring system for the Blood-Borne Virus Transmission Risk Assessment Questionnaire (BBV-TRAQ): Applications for community-based HCV surveillance, education and prevention - Stoové, Mark A (BioMed Central, 2008)
BACKGROUND: The hepatitis C virus (HCV) is a major cause of drug-related morbidity and mortality, with incidence data implicating a wide range of HCV transmission risk practices. The Blood-Borne Virus Transmission Risk Assessment Questionnaire (BBV-TRAQ) is a content valid instrument that comprehensively assesses HCV risk practices. This study examines the properties of a new weighted BBV-TRAQ designed to quantify HCV transmission risk among injecting drug users (IDU). METHODS: Analyses of cross-sectional surveys of Australian IDU (N = 450) were used to generate normative data and explore the properties of a weighted BBV-TRAQ. Items weights were assigned according to expert key informant ratings of HCV risk practices performed during the development stages of the BBV-TRAQ. A range of item weights was tested and psychometric properties explored. A weighting scheme was recommended based on the plausibility of normative subscale data in relation to research evidence and the ability of BBV-TRAQ scores to discriminate between HCV positive and negative participants. RESULTS: While retaining the psychometric properties of the unweighted scale and demonstrating good internal reliability. By taking into account the relative transmission risk of a broad range of putative HCV practices, the weighted BBV-TRAQ produced promising predictive validity results among IDU based on self-report HCV status, particularly among young and less experienced injectors. CONCLUSION: Brief, easy to administer and score, and inexpensive to apply, the utility of the BBV-TRAQ for community based education and prevention is enhanced by the application of item weights, potentially offering a valid surrogate measure for HCV infection among IDU.